The Phenomenological Analysis of the Impact of Digital Overstimulation on Attention Control in Elementary School Students: A Study on the 'Brain Rot' Phenomenon in the Learning Process - Eogenie Lakilaki; Roza Melinda Puri; Angga Nuraufa Zamzami Saputra; Ayu Nur Shawmi; Nur Asiah; Muhammad Rizky (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study examines the impact of digital overstimulation on attention control in elementary school students, particularly concerning the phenomenon of